KOMPETENSI KEPRIBADIAN GURU DALAM MENGAJAR TERHADAP TINGKAT KEDISIPLINAN BELAJAR SISWA KELAS VIII MTS AL BANNA PULAU BANYAK - Marhan Hasibuan; sinta (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
This certainly affects the behavior of students who seem less disciplined in their learning activities. Both in terms of coming to school and in doing the assignments given by the teacher. Students do not have role models that must really be emulated so that they act according to their wishes. This type of research is quantitative research, data collection methods by means of observation, interviews, and questionnaires. Data analysis techniques by means of statistical tests to find research results. The result of the research is that there is a positive and significant relationship. The discipline level of student learning at MTs Al Banna Pulau Banyak has a mean result of 52.7, the median is 53.6, the mode is 53, the variance is 17.85 and the standard deviation is 4.22 which is acceptable. with limits indicating positive and significant tolerance. There is a positive and significant relationship between the variables related to the teacher's personality competence in teaching and the level of student learning discipline at MTs Al Banna Pulau Banyak with the regression line Y = 22.37 +0.61 X. There is a significant correlation between the teacher's personality competence and the level of discipline student learning at MTs Al Banna Pulau Banyak after carrying out a regression test with the product moment formula with a calculated result of 0.833 with a strong or high level of relationship.